The Analysis of Employee Performance at Semarang Religious Training Center - Rukhana Fitriati (Indonesian Association for Public Administration (IAPA), 2020)
Employees play a significant factor for the success of an organization in any organization. Therefore, it is necessary to achieve good performance of employees in a company. Performance is a completion of official tasks and duties to achieve organizational goals. This study analyzed the performance of employees at Semarang Religious Education and Training Center and which aimed to find a solution on how to improve the performance of employees at Semarang Religious Education and Training Center. The research method used was qualitative with qualitative descriptive approach. The results showed that work performance, skills, behavior, abilities and motivation aspects were still not good enough. Moreover, the solution to improve employee performance are such as adding the quantity of employees to help older employees to work, work placement must be based on their educational background, employees’ initiatives need to be always encouraged, and holding some programmed team work improvement activities. In addition, it is necessary to conduct special training programs to increase the ability of employees in their own workfields to improve the employees’ skills and a motivation training program to increase employees’ motivation.